1989
DOI: 10.1037/h0091742
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for the use of Bayesian probabilities in neuropsychological assessment.

Abstract: A measurement model based on Bayesian probabilities is proposed as an alternative to approaches based on classical measurement theory. The suggested model includes use of interactive microcomputer programs to integrate clinical im~ pressions into the metric assessment procedure. The Bayesian model provides a new focus in neuropsychological assessment for both cognitive and affective functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The implications of Bayes' theorem for clinical neuropsychological diagnosis have been discussed as early as in 1955 (Crawford, Garthwaite, & Betkowska, 2009;Elwood, 1993;Frederick & Bowden, 2009;Gavett, 2015;Gordon, 1977;Gouvier, 2001;Ivnik et al, 2001;Jones, 1989;Labarge et al, 2003;Meehl & Rosen, 1955;O'Bryant & Lucas, 2006;Satz et al, 1970;Slick, 2006). Despite these early insights, a review in 2003 observed that it was uncommon to consider the impact of base rates in diagnostic accuracy studies (Woods et al, 2003).…”
Section: Bayesian Diagnostic Decisions Are Informed By Prior Beliefsmentioning
confidence: 99%
See 2 more Smart Citations
“…The implications of Bayes' theorem for clinical neuropsychological diagnosis have been discussed as early as in 1955 (Crawford, Garthwaite, & Betkowska, 2009;Elwood, 1993;Frederick & Bowden, 2009;Gavett, 2015;Gordon, 1977;Gouvier, 2001;Ivnik et al, 2001;Jones, 1989;Labarge et al, 2003;Meehl & Rosen, 1955;O'Bryant & Lucas, 2006;Satz et al, 1970;Slick, 2006). Despite these early insights, a review in 2003 observed that it was uncommon to consider the impact of base rates in diagnostic accuracy studies (Woods et al, 2003).…”
Section: Bayesian Diagnostic Decisions Are Informed By Prior Beliefsmentioning
confidence: 99%
“…Although Bayes theorem is not new in the field of neuropsychology (e.g., Elwood, 1993;Gavett, 2015;Gelman & Geurts, 2017;Jones, 1989), Bayesian hypothesis testing has received less attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation